Knowledge and Attitudes Regarding Pubertal Changes among Adolescent Males in Karachi: A Study Protocol. - Nazim, Sabah Muhammad; Gulzar, Saleema; Ahmed Khuwaja, Hussain Maqbool; Lassi, Zohra S. (Journal of Asian Midwives, 2024)
Background: Adolescence (the period between childhood and adulthood) is characterized by significant changes in bodily functions, along with psychological and cognitive growth, which lays the foundation for future health. The unanticipated changes in that phase (especially related to sexuality) can cause adolescents embarrassment and distress, thus impacting their well-being and development. Despite the critical role of puberty in adolescents’ physical, psychological, and social development, research focusing on the knowledge and experiences of male adolescents going through puberty is limited, especially in urban Karachi, Pakistan. Several Pakistani studies have mainly focused on female adolescents and their experiences with puberty, leaving a significant gap in understanding the knowledge and attitudes of male adolescents towards pubertal health and its changes. This gap in research is problematic since it hinders the development of effective health interventions and education programs that target male Pakistani adolescents to improve their pubertal health outcomes. Therefore, this study will assess the level of knowledge of male students and their attitudes toward puberty and its associated changes. Methodology: The study will follow a quantitative descriptive cross-sectional design. The study setting will be Karachi, where participants will be recruited from four study sites: two private secondary schools, and two government schools. A total of 270 male adolescents will be part of the research program, selected using a stratified random sampling method. Students in grades 8, 9, and 10 aged 14 to 17 years, will be included in the study as per the inclusion criteria. A researcher-developed questionnaire will be used to survey the participants. The collected data will be analyzed through descriptive statistical analyses. Conclusion: Puberty, which is marked by rapid physical and sexual development, is a universal experience for all humans. Inadequate knowledge and education regarding this critical stage of life can leave one unprepared for the transformations that come with it. Several Pakistani studies have mainly focused on female adolescents and their experiences with puberty; however, research focusing on the knowledge and experiences of male adolescents going through puberty is limited, especially in Karachi, Pakistan. This gap in research is problematic since it hinders the development of effective health interventions and education programs that target male Pakistani adolescents to improve their pubertal health outcomes.